(untitled) (Tri-Chandra Journal of Anthropology, 2025)
This study examines the multifaceted impacts and challenges faced by Dupcheshwor Rural Municipality in the aftermath of the 2072 Gorkha Earthquake, with a focus on both immediate and long-term consequences for the local population. It adopts a descriptive research design and a mixed-methods approach, combining qualitative and quantitative data collected from 200 randomly selected households. Primary data were gathered through semi-structured interviews and focus group discussions, while secondary data were sourced from government reports, NGO assessments, and academic literature. The core findings reveal extensive destruction of homes, infrastructure, and agricultural assets, which significantly disrupted livelihoods and heightened food insecurity. Access to essential services such as healthcare, education, water, and sanitation was severely affected. Displacement and the breakdown of essential community services further complicated the recovery process. Beyond physical and economic hardships, the earthquake also had profound psychosocial impacts, particularly among women, children, and the elderly, who experienced elevated levels of trauma and emotional distress. Despite these challenges, local communities demonstrated notable resilience through mutual aid, informal networks, and self-initiated recovery efforts. However, institutional responses were hindered by inefficiencies, poor coordination, and limited reach, particularly in remote and marginalized areas. The study underscores the urgent need for comprehensive and inclusive disaster risk reduction strategies that prioritize community-based approaches, strengthen local institutional capacities, and address both structural vulnerabilities and psychosocial needs. The findings contribute to broader discussions on disaster governance by emphasizing the importance of resilience-building and equitable recovery planning in rural, disaster-prone settings.